High-Performance Reconfigurable Piezoelectric Resonators and Filters for RF Frontend Applications - Fouladi Azarnaminy, Arash (University of Waterloo, 2022)
A conventional RF frontend module consists of many filters where each filter is allocated for a specific frequency band. These filters are connected through multiplexing switch networks to support multi-band wireless standards. Using an individual filter for each frequency band increases the module size, power consumption and cost. Therefore, implementation of reconfigurable filters that can operate at different frequency bands while maintaining key RF performance requirements such as low insertion loss, good linearity and power handling is necessary for manufacturing of future RF frontends. Acoustic wave resonators based on piezoelectric devices such as Surface Acoustic Wave (SAW) and Bulk Acoustic Wave (BAW) are the most commonly used technologies to manufacture filters for RF applications. The objective of the research described in this thesis is to investigate the feasibility of tunable filter solutions using piezoelectric SAW resonators. A tunable SAW technology which can maintain required performance parameters and can be commercially manufactured will constitute a technological breakthrough in wireless communications. Thin-Film Piezoelectric on Substrate (TPoS) resonators, based on Aluminum Nitride (AlN) piezoelectric material which are fabricated using commercially available Silicon on Insulator (SOI) PiezoMUMPs process, have been demonstrated. By combining the superior acoustic properties of AlN and single crystalline silicon substrate, this class of resonators achieves ultra-high quality factor (Q) values in excess of 3600. A 3-pole bandpass filter using direct electrical coupling between the resonators has been presented and we have studied the performance of the fabricated filter over a temperature range from -196ºC up to +120ºC and under high power. For the first time, we have demonstrated the integration of switching elements, based on Vanadium Dioxide (VO2) phase change material, with Incredible-High-Performance SAW (IHP-SAW) technology which allows us to design and implement switchable and reconfigurable SAW resonators and filters for wireless applications. Switchable multi-band filters using VO2 switches strategically imbedded within the resonators of the filter have been demonstrated. A switchable dual-band filter with four switching states and two channels was presented using hybrid integration approach where discrete VO2 switches were fabricated separately and then integrated with the SAW resonators and filters using wire bonds. The fabricated 5-pole dual-band filter demonstrated good insertion loss in both transmission states but had inadequate performance in terms of isolation between the channels due to the limitations of the hybrid integration approach. Moreover, hybrid integration does not allow us to use more than a few switching elements and cannot be used for the implementation of higher order filters. To address these issues, we have demonstrated the monolithic integration of VO2 switches using an in-house fabrication process that allows us to fabricate VO2 switches and SAW resonators and filters on a single chip. A dual-band switchable higher order 7-pole filter with six monolithically integrated VO2 switches, three for each channel, was demonstrated. The monolithic integration allows the single-chip implementation of the proposed switchable dual-band filter with improved performance along with significant size reduction and ease of manufacturing, paving the path for commercialization of this technology. Novel reconfigurable SAW resonators and filters with tunable center frequency were also presented for the first time. Tuning of the center frequency between two different states was achieved by changing the configuration of interdigitated electrodes within the SAW resonator and by using a set of tuning electrodes and VO2 switches. In the first implementation, the VO2 switches were integrated over the electrodes and inside the active area of the SAW resonator. Each resonator consists of hundreds of tuning electrodes and for a reliable switching each resonator requires a number of heater elements which results in increased DC power consumption and total size. A second reconfigurable resonator with a modified structure and using a modified in-house fabrication process to include a second electrode layer was proposed to reduce the number of required VO2 switching elements for an even more compact implementation and ten times reduction in the required DC power consumption. Design, implementation, and measurement results for a 3-pole tunable SAW filter based on the proposed reconfigurable resonators have been presented. The filter’s center frequency is tuned from 733 MHz to 713 MHz while the insertion loss was maintained below 2.5 dB. The fabricated SAW resonators and filters also showed acceptable linear and high-power performance characteristics. This is the first time a single-chip implementation of a reconfigurable SAW filter with center frequency tuning and acceptable RF performance using monolithically integrated VO2 switches is ever reported. The single-chip implementation of the proposed SAW resonators and filters enables the development of future low-cost RF multi-band transceivers with improved performance and functionality.
Keywords: Surface acoustic wave devices; Piezoelectric resonators; Tunable filters; Reconfigurable RF circuits